Teaching with Multiple Choice Questions. - Jarnagin, Bill D.; Harris, John K. (The Accounting Review, 1977)
ABSTRACT: Multiple choice questions, in contrast to problems and discussion questions, permit coverage of a greater breadth of topics in a given time period and reduce grading workload; however, the basis of the conventional multiple choice answer is not elaborated. Preparing this elaboration can be a valuable learning experience. This article describes and illustrates a technique that guides the accounting student's preparation of elaborated multiple choice answers. The technique can be adapted for both examination and assignment purposes, with the benefits far exceeding the costs in either use.